An investigation of the effectiveness of TWA on reading comprehension of students with and at-risk for emotional and behavioral disorders - Sanders, Sara (Kansas State University, 2018)
Students with emotional and behavioral disorders frequently display deficits in reading. One emerging method for addressing these deficits is known as self-regulated strategy development (SRSD). One specific SRSD reading strategy is TWA (Think before reading, think While reading, and think After reading), which teaches students to self-monitor and self-evaluate while reading. The purpose of this study was to determine if TWA is effective in increasing reading comprehension of fourth, fifth, and sixth grade students with or at-risk for emotional and behavioral disorders, using a randomized control trial pretest-posttest design. Results suggested no statistical significance between the reading comprehension of the treatment and control group following the intervention. Limitations are discussed and suggestions for future research are presented.
Keywords: Self-regulated strategy development (SRSD); Elementary; Emotional and behavioral disorders (EBD); Reading comprehension; Reading strategy; Self-regulation